Survival of urban women under ESAP in Masvingo, Zimbabwe - Muzvidziwa, Victor N. (International Institute for Human Factor Development, 2016)
Perhaps because the impact of the Economic Structural Adjustment Program (ESAP) in Zimbabwe has been particularly negative and has affected women more than men, female heads of households in Masvingo responded by mobilizing and gearing themselves to meet the challenges of ESAP. While the majority of the women in my study continued to struggle to subsist in town under deteriorating socio-economic conditions, contrary to expectations a minority of female heads of households in my study managed not just to cope with urban poverty, but to climb out of poverty. ESAP for this successful minority might thus have produced a long-term, positive, but unintended effect of empowering women within the economic field. ESAP in a minority of cases might be the stimulant to the growing economic independence of women in cities. The paper argues that despite the limited successes it is important to guard against the tendency to exaggerate the capacity of women to survive in urban environments under ESAP.